2019
DOI: 10.4103/1673-5374.251333
|View full text |Cite|
|
Sign up to set email alerts
|

A high methionine, low folate and vitamin B6/B12 containing diet can be associated with memory loss by epigenetic silencing of netrin-1

Abstract: Memory-epigenetics which is the loss of memory due to epigenetic modifications can be due to the silencing of genes involved in cognitive functions and this is the basis of the current study. We hypothesize that a diet containing high methionine and low vitamins can lead to memory impairment by increasing global DNA methylation and therefore, silencing the netrin-1 gene, which encodes the glycoprotein involved in neurogenesis, axonal guidance and maintenance of the synaptic plasticity. Wild type (C57BL/6J) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Furthermore, exogenous application of netrin-1 has been found to regulate Aβ peptide production, oligomerization and clearance in AD models, to improve cognitive dysfunction as assessed in the novel object recognition task and ameliorate impaired spatial memory as demonstrated in the morris water maze test (Lourenço et al, 2009;Spilman et al, 2016;Shabani et al, 2017;Zamani et al, 2019). Previous data also indicates that down-regulation of netrin-1 attribute to hyper-methylation of its gene can result in memory loss (Kalani et al, 2019). In addition, netrin-1 protected Aβ1-42-exposed SH-SY5Y cells through NF-κB/Nrf2 dependent mechanism (Zamani et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, exogenous application of netrin-1 has been found to regulate Aβ peptide production, oligomerization and clearance in AD models, to improve cognitive dysfunction as assessed in the novel object recognition task and ameliorate impaired spatial memory as demonstrated in the morris water maze test (Lourenço et al, 2009;Spilman et al, 2016;Shabani et al, 2017;Zamani et al, 2019). Previous data also indicates that down-regulation of netrin-1 attribute to hyper-methylation of its gene can result in memory loss (Kalani et al, 2019). In addition, netrin-1 protected Aβ1-42-exposed SH-SY5Y cells through NF-κB/Nrf2 dependent mechanism (Zamani et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Evidence suggests that Met promotes neuroinflammation and impairs neurogenesis [ 91 ]. Met is also associated with memory loss [ 92 ], due to the alteration of methylation patterns, and thus the expression of Netrin-1, which is involved in neuronal processes. Since Netrin-1 inhibits mTORC1 [ 93 ], these results suggest that memory impairment in AD might be associated with hyperactivation of mTORC.…”
Section: Mtorc1 and Nutritional Interventions In Pathological Processesmentioning
confidence: 99%
“…WEGN can aid in biological processes, such as improving cognitive function, strengthening immunity, and remodeling the gut microbiota. [26][27][28][29][30] Previous studies have shown that WEGN aids in antioxidation, maintaining the choline balance, reducing neuronal damage, and restoring the memory impairment of AD model rats induced by D-gal combined with AlCl 3 . 31 Despite the beneficial pharmacological effects of the WEGN, its mechanism in relieving AD is unclear.…”
Section: Introductionmentioning
confidence: 99%